2020
DOI: 10.14366/usg.19010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lymph node metastasis in a rabbit tumor model: correlations between contrast-enhanced ultrasound and pathologic findings

Abstract: Purpose: The purpose of this study was to evaluate the ability of contrast-enhanced ultrasonography (CEUS) with microbubbles to detect metastatic lymph nodes (LNs) for treatment planning and prognosis. Methods: For the metastatic LN model, ground VX 2 tumor tissues were injected subcutaneously in 12 rabbits, just below the right hind limb. The rabbits were classified into three groups based on the LN area: group A (n=4, >1.9 cm 2 ), group B (n=4, 1-1.9 cm 2 ), and group C (n=4, <1 cm 2 ). The LNs were monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The results indicated that the enhancement of nonmetastatic SLNs tended to be type I with homogeneous enhancement, while that of metastatic SLNs tended to be type II or III with heterogeneous enhancement. The reason for this finding may be that lymph node metastasis is mainly caused by tumor cells entering lymph nodes through LCs, which leads to the destruction of the normal structure of lymph nodes ( 23 ). In this case, the contrast agent cannot flow into the tissue after entering LCs, thus forming filling defects.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the enhancement of nonmetastatic SLNs tended to be type I with homogeneous enhancement, while that of metastatic SLNs tended to be type II or III with heterogeneous enhancement. The reason for this finding may be that lymph node metastasis is mainly caused by tumor cells entering lymph nodes through LCs, which leads to the destruction of the normal structure of lymph nodes ( 23 ). In this case, the contrast agent cannot flow into the tissue after entering LCs, thus forming filling defects.…”
Section: Discussionmentioning
confidence: 99%
“…77 Consequently, in the burgeoning era of tumour immunotherapy, it is crucial to establish effective in vivo models such as mice, 97 zebrafish, 98 or rabbits. 99 Regarding in vitro research, the limitations of 2D cell culture models have driven the development of 3D models, which better mimic the natural tissue's cellular microenvironment. Spheroids, organoids, and 3D bioprinting are commonly used methods for creating 3D models, with substantial potential for studying LNM.…”
Section: Research On Lnmmentioning
confidence: 99%
“…Recent research posits that the lymph node is more than a passive staging area during metastasis; it is a crucial site for initiating systemic immunosuppression 77 . Consequently, in the burgeoning era of tumour immunotherapy, it is crucial to establish effective in vivo models such as mice, 97 zebrafish, 98 or rabbits 99 . Regarding in vitro research, the limitations of 2D cell culture models have driven the development of 3D models, which better mimic the natural tissue's cellular microenvironment.…”
Section: Dilemmas and Prospectsmentioning
confidence: 99%
“…Additionally, contrast-enhanced US (CEUS) refers to the application of US contrast agents in medical US. CEUS can provide anatomic information with gray-scale US and physiologic information through the SDUS, CDUS, and PDUS techniques, making it indispensable in the assessment of vascular pathology [15][16][17][18][19][20][21]. The presence of a microbubble US contrast agent in the vasculature enhances the backscattering of US waves, resulting in a marked amplification of flow signals and providing information on the microvasculature [12,21,22].…”
Section: Basic Principles and Techniques Of Doppler Usmentioning
confidence: 99%
“…The emerging modality of SMI can reveal more vascular details than CDUS or PDUS [ 33 - 35 ]. However, the populations in previous studies had a wide range of prevalence of papillary thyroid carcinomas (63.3%-90.6%) [ 16 , 44 - 46 ]. The parameters of SDUS, including PI and RI, may be important in differentiating benign from malignant thyroid nodules [ 28 , 29 , 31 , 38 , 39 ].…”
Section: Clinical Applications Of Doppler Usmentioning
confidence: 99%